ANALISIS PREVENTIVE PANEL DAN GENERATOR 3 PHASA PADA PT. PERTAMINA HULU ENERGI OGAN KOMERING - Dinda Tri Hasanah Sihombing; Muhammad farhan; Reihan Akbar Sitompul; Arwadi Sinuraya; Desman Jonto Sinaga (JOURNAL SAINS STUDENT RESEARCH, 2025)
. This Industrial Internship was carried out at PT. Pertamina Hulu Energi Ogan Komering, focusing on the implementation of preventive maintenance on the electrical system, particularly the generator and Power Generation Unit (PGU) panel. The objectives of this activity were to understand the application of preventive maintenance, analyze the condition and performance of the electrical system, and evaluate the effectiveness of the maintenance program in ensuring operational reliability. The method included visual inspections, electrical parameter measurements (voltage, current, temperature, and battery voltage), as well as protection function and cooling system testing. Measurement data collected over 30 days indicated that the system operated within normal limits, with phase-to-phase voltages ranging from 375–389 V, phase currents between 23–26 A, and component temperatures between 26–27°C. The evaluation results showed that preventive maintenance successfully reduced the risk of sudden failures, extended equipment lifespan, and maintained electrical distribution efficiency. The implementation of this program proved effective in enhancing system reliability, minimizing downtime, and supporting smooth oil and gas production operations within the company.